Fostering Academic Peer Exchange in Distance Learning - Heidi Rinn; Ricarda Schlimbach; Susanne Robra-Bissantz; Daniel Markgraf (FernUniversität Hagen, 2023)
Virtual worlds (VWs) have been present in higher education for more than a decade but have regained substantial traction in recent years as a result of COVID-19 and the metaverse hype. Nonetheless, facilitating peer exchange and social interaction in VWs in higher education has not been sufficiently researched nor is specific design knowledge available. Therefore, we derive design principles systematically by collecting design requirements based on scientific contributions on VWs, encompassing the instructor viewpoint, before turning them into meta-requirements that we then merge to design principles. We translate these into tangible design features instantiated in a genuine VW teaching unit with master students. The evaluation in focus group interviews after the application of our design knowledge demonstrates the theoretical and practical value of our contribution to strengthening social interaction in distance learning settings from teachers' and learners' perspectives.